The Study of Personality in Addicts and Normal Group with Due Attention to Gender - Nafiseh Mirfakhraei; Zeinab Khanjani; Rahim Badri (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The aim of this study was the comparison of personality traits in addicts and normal group whit due attention to gender. Materials & Methods: The design of the present study was a causal comparative that has been done on the 90 people (60 men and 30 women addicts with the range of age=20-40) of the referrers to the welfare centers and outpatient addiction treatment centers in different parts of Tabriz and Marand in1388. They were selected through the accessible sampling method. This group suffered the substance abuse or dependence on Amphetamine substance on basic of the diagnosis criterions DSM-IV-TR. The other group, 60 men and 30 women with non-addicted who were among the relatives, neighbors and friends. The number of all members was 180 people. An assembling instrument was questionnaire of NEO-FFI. Analysis of the data was based on the multiple-analysis of variance (MANOVA) and LSD post-hock test. Results: The results revealed that there was significant difference between addicts and normal group in personality traits. Addicted scores were high neuroticism (P<0.001), less openness to experiences (P<0.001), less agreeableness (P<0.001), less conscientiousness (P0.05). Also, the results revealed that women scores were higher in neuroticism (P<0.05), agreeableness (P<0.05), and conscientiousness (P<0.001), than men and men score was higher in openness to experiences.  Conclusion: Addiction as a social pathology will not be eradicate completely, but it can be controlled through thinking, devotedly attempts. An assessment of personality traits in addicts contributes important information for a better definition and recognition of addicts and has implications for their treatment.